Effect of stress ratio on fatigue crack growth of Ti40 alloy - 吴欢 赵永庆 曾卫东 (Transactions of Nonferrous Metals Society of China, 2007)
The effect of stress ratio on fatigue crack growth （FCG） behavior of Ti40 alloy was analyzed. A unified approach, developed by VASUDEVAN and SADANANDA was used. The approach is based on the realization that fatigue requires two load parameters for unambiguous description. They are two fracture mechanics parameters： the maximum stress intensity factor K~ and the stress intensity amplitude AK. The results show that there are two mechanisms controlling the FCG behavior of Ti40 alloy. The curves of the two mechanisms in trajectory map are similar. They deviate to Kmax axial more strongly compared with other titanium alloy, which indicates that Ti40 alloy is more sensitive to environment.